TELAAH TOPIK STOIKIOMETRI SMA: MISKONSEPSI DAN STRATEGI PEMBELAJARANNYA - Indah R Anugrah (Orbital: Jurnal Pendidikan Kimia, 2019)
The problem of student’s misconceptions of stoichiometry is still happening even though there have been so many studies done for identify misconception experienced by students. It is because most of those research is only focused on revealing student’saomisconceptions. The purpose ofathisastudyais to identifyatheatendency ofomisconceptions experienced by studentsuanduexamineatheaappropriate learning strategies that can be applied to avoid those misconceptions. Comparative study is performed to determine misconceptions appeared in the identification process through various diagnostic instruments, namely two-tier test, three-tier test and certainty of response index. Thearesultiofothispstudy showsithatimost of misconceptions appeared because rstudents are too focused on the algorithmic aspects and put aside the conceptual aspects in solving stoichiometric problems. It is caused by the instruction process which emphasizes the success of using formulas to solve numeric problems so students ignore understanding of related concepts. The use of chemical representation visualization through student-generated sub-micro diagrams is considered capable of being a link between macroscopic and symbolic phenomena so as to enhance students’s understanding of concepts related to stoichiometry.